Sustainable Financing as a Mechanism to Increase Private Participation in the Development of Infrastructure Systems in the Water Sector (2016)
This work addresses the problem of the coverage gap in the water sector in Colombia and how the creation of an eco-innovative financing mechanism aligned with Sustainable Development Objectives (particularly objectives 6 and 9) can encourage the private sector’s involvement, boosting the development of a sustainable infrastructure to help bridge the coverage gap. Therefore, this project’s primary objective is based on making a methodological contribution that encourages lenders to promote the development of sustainable infrastructure and the capture of financial value, as measured by the Financial Capture Value Theory, by financing water infrastructure systems with a special focus on Colombia. To create and validate the methodological proposal, it was necessary to clarify the theoretical concepts of financial eco-innovations; therefore, the main elements of sustainable financing from the financial eco-innovation perspective as a strategy to develop sustainable infrastructure were analyzed. In addition, a detailed study of the current state-of-art Colombia’s water sector and the private involvement through Public-Private Partnerships, which enabled identification of the main elements, characteristics and investment needs in the sector, was conducted. In this way, this research proposes a methodology of sustainable financing as a mechanism to increase the private participation in the development of infrastructure systems in the Colombian water sector using a mezzanine-type debt mechanism (incorporating the Water Criteria of the Climate Bonds Standard). The methodology is validated by being implemented in a project in Colombia’s water sector.